Effects of go-green campaigns on changing attitude towards green behaviour - Rezai, Golnaz; Hosseinpour, Masoumeh; Shamsudin, Mad Nasir; Abd Latif, Ismail; Sharifuddin, Juwaidah (Universiti Putra Malaysia Press, 2015)
A lot of effort has been made by the Malaysian government via go-green campaigns to relay the importance of green behaviour to society. Go-green campaigns have been in force over the last three decades but the effectiveness of such campaigns is yet to be determined. This study seeks to uncover the association between the socio-demographic characteristics and the respondents' attitude towards green behaviour based on the information they received through the go-green campaigns. A structured questionnaire was designed as the instrument to gather data for this study. A conceptual model was developed to identify the variables that were likely to affect the respondents' attitude and decisions on adopting green behaviour. One thousand two hundred and six (1,206) respondents were administered randomly to discover their intention of performing green behaviour following the go-green campaigns. Chi-square and the binary logistic regression model were applied to answer the study objectives. The results show that selected socio-demographic profiles such as age and marital status significantly affect the respondents' intention towards performing green behaviour.